Interest Rate Liberalization, Quality institutions and Stock Market Development in Selected Sub-Saharan African Countries - Balogun, Wakilat Olabisi; Dahalan, Jauhari B.; Hassan, Sallahuddin B. (International Journal of Economics and Financial Issues, 2016)
The paper examines the long run effects of interest rate liberalization and institutional quality on the development of stock market in seven selected sub-Saharan African countries using panel dataset that spans 1990 to 2013. The study employs dynamic heterogeneous panel method using the technique of Pooled Mean Group (PMG). The results reveal that on the average liberalizing the interest rates has a negative long run impact on the development of the stock markets in the seven selected SSA economies. Institutional quality on the other hand has significant positive relationship with the development of stock market. The policy recommendation as a result of this finding is that liberalization of interest rates in the SSA region should be a guided one. Keywords: Interest rate, institutional quality, stock market development. JEL Classifications: F35, F65, G15.